2018
DOI: 10.3390/jfmk3010017
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast Formation within a Human Co-Culture System on Bone Material as an In Vitro Model for Bone Remodeling Processes

Abstract: Bone remodeling can be mimicked in vitro by co-culture models. Based on bone cells, such co-cultures help to study synergistic morphological changes and the impact of materials and applied substances. Hence, we examined the formation of osteoclasts on bovine bone materials to prove the bone resorption functionality of the osteoclasts in three different co-culture setups using human monocytes (hMCs) and (I) human mesenchymal stem cells (hMSCs), (II) osteogenic differentiated hMSCs (hOBs), and (III) hOBs in addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The last approach uses bone‐like materials (bone slices) allowing the achievement of functional human osteoclasts with characteristic actin morphology and the expression of cathepsin K and CD51/61. This approach very closely replicates the in vivo situation [23].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The last approach uses bone‐like materials (bone slices) allowing the achievement of functional human osteoclasts with characteristic actin morphology and the expression of cathepsin K and CD51/61. This approach very closely replicates the in vivo situation [23].…”
Section: Introductionmentioning
confidence: 85%
“…The co‐culture was then performed in the differentiated medium by adding osteoclastogenic differentiation factors including macrophage colony‐stimulating factor (50 ng/ml) and receptor activator of nuclear factor K‐B ligand (50 ng/ml). The medium was exchanged every 2–3 days until day 28 [23]. For the bone model with induced cancer, cancer cells were added on day 25 into the bone model by replacing 50% of the medium with the new medium containing CEM cells (1.5 × 10 3 cells/well) [24].…”
Section: Methodsmentioning
confidence: 99%
“…However, the possible side effects of exposing donors to these pharmacological agents might not be ethical for the donors [83]. Luckily, monocytes that are derived from HSCs and comprise 10-20% of peripheral blood mononuclear cells can be directly isolated from peripheral blood and have been used as osteoclast precursor cells in in vitro studies [136][137][138][139][140][141][142]. To isolate HSCs from bone marrow and peripheral blood, several protocols have been developed including direct plating of bone marrow aspirates and blood samples on plastic surface and collecting the non-adherent cells as it has been shown that HSCs are less likely to attach to the plastic substrate compared with MSCs.…”
Section: Bone Marrow-derived Hscs Vs Peripheral Blood-derived Hscsmentioning
confidence: 99%
“…Another method is culturing mononuclear cells separated via density gradient centrifugation under osteoclastogenic culture condition which led to the generation of osteoclasts in culture [145,146]. Moreover, HSCs and monocytes can be isolated and purified based on the expression of their own specific surface marker such as CD34 and CD14 using techniques including an automated magnetic purification system and FACS [124,125,[136][137][138][147][148][149][150].…”
Section: Bone Marrow-derived Hscs Vs Peripheral Blood-derived Hscsmentioning
confidence: 99%
“…Several in vitro models describe the e昀昀ect of mechanical stimuli on OCs, di昀昀ering in their analytical techniques and methodologies. These models include the direct e昀昀ect of mechanical stimuli on the behavior of osteoclast-like cells, substrate or sca昀昀old deformation on which the cells are grown [10], 昀氀uid 昀氀ow shear stress-induced formation of osteoclasts [11], and centrifugal compression applied to PDL 昀椀broblasts. Despite all of these in vitro models being used to investigate the e昀昀ects of mechanical stimuli on bone cells, the mechanisms whereby mechanical forces trigger a response on OCs and the nature of this response remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%